2021
DOI: 10.1536/ihj.20-434
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Cardiac Strain and Contractility After Hematopoietic Stem Cell Transplantation in Patients with Hematologic Malignancies

Abstract: Hematopoietic stem cell transplantation (HSCT) is occasionally associated with cardiac dysfunction during long-term follow-up. Global longitudinal strain (GLS) has emerged as an early predictor of cardiotoxicity associated with cancer therapy; however, the serial changes in GLS before and after HSCT have not been elucidated. To clarify the association between HSCT and GLS, we investigated serial changes in GLS before and after HSCT. We evaluated cardiac function before and 1, 3, and 6 months after HSCT in 38 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Interesting data were obtained by Oka et al, who examined serial changes in cardiac strain and contractility in patients with hematologic malignancies after hematopoietic stem cell transplantation (HSCT). They found that GLS before HSCT might be associated with a decrease in LVEF after HSCT [32]. The results from a study on patients with colorectal cancer confirmed the usefulness of GLS in the diagnosis of bevacizumab-induced cardiotoxicity [33].…”
Section: The Use Of Gls Assessment In Patients With Various Cancersmentioning
confidence: 77%
“…Interesting data were obtained by Oka et al, who examined serial changes in cardiac strain and contractility in patients with hematologic malignancies after hematopoietic stem cell transplantation (HSCT). They found that GLS before HSCT might be associated with a decrease in LVEF after HSCT [32]. The results from a study on patients with colorectal cancer confirmed the usefulness of GLS in the diagnosis of bevacizumab-induced cardiotoxicity [33].…”
Section: The Use Of Gls Assessment In Patients With Various Cancersmentioning
confidence: 77%
“…Subtle deterioration in LV systolic function may be better detected by the global longitudinal strain method. 31 Second, this was a single-centre retrospective study with a limited number of patients, and patients without echocardiography before or after HSCT were excluded. As echocardiography was performed at a physician's discretion, participant enrolment may have potentially led to a selection bias.…”
Section: Limitationsmentioning
confidence: 99%